Warehouse Inventory Recording System Based on VBA Excel at Sinar Mas Berau Coal Polytechnic - Dewi Safitriani; Nur Ainun Musvirah; Hamim Rachman (Poltanesa, 2026)
Effective inventory management is a crucial aspect in supporting smooth logistics operations, including in vocational education institutions such as Politeknik Sinar Mas Berau Coal. However, manual inventory recording is still a common obstacle, especially in terms of efficiency, data accuracy, and ease of tracking goods. This study aims to design and implement a warehouse inventory recording system based on Microsoft Excel with Visual Basic for Applications (VBA) support to improve recording efficiency and accuracy. This system is designed to document incoming and outgoing goods data, monitor stock in real-time, and present integrated automatic reports. The implementation results show that this VBA Excel-based system is able to simplify the warehouse administration process, minimize the risk of data input errors, and simplify the internal logistics audit process. This system can also be an economical and applicable solution for educational institutions with limited resources. In the future, this system can be further developed with database integration and higher security features.